Application of a Deep Eutectic Solvent for the Synthesis of Novel Imidazole-Containing Quinazoline Derivatives as Potent Cytotoxic Agents - Fatemeh Azmian Moghadam; Sara Dabirian; Amin Ebrahimi Tavani; Parisa Alipour; Mohammad Mojabi; Mehdi Evazalipour; Fatemeh Yousefbeyk; Saeed Ghasemi (Tabriz University of Medical Sciences, 2024)
Background: Drugs containing the 4-anilinoquinazolines scaffold play a critical role in cancer treatment by inhibiting protein kinases, especially tyrosine kinases. In this study, a novel series of 4-anilinoquinazoline derivatives were synthesized and evaluated as cytotoxic agents. Methods: All final compounds were synthesized using two methods, including a conventional approach using potassium iodide and dimethylformamide as well as a green method using a deep eutectic solvent (DES) comprising choline chloride: urea. The cytotoxicity was tested on the A431, HUVEC, and HU02 cell lines. To evaluate the binding pattern of the compounds with EGFR and VEGFR-2, a molecular docking investigation was performed. Finally, the wound healing assay was carried out to assess the potency of compounds in inhibiting cell migration. Results: The final reaction time was approximately 15-20 min with yields of 60-72% using DES, while the conventional method took 3 to 4 h to complete, with yields between 30% and 42%. Compounds 8k and 8l showed better cytotoxicity against both cell lines compared to vandetanib (IC50=0.11 µM and 0.26 µM on A431 and IC50=5.01 µM and 5.24 µM on HUVEC, respectively). Molecular docking studies revealed that compound 8k, which contained 3-methylaniline at the 4-position of the quinazoline core, showed efficient binding affinity to both EGFR and VEGFR-2. An essential hydrogen bond was formed between quinazoline N1 of 8k and the Met796 residue of EGFR with a docking score of -8.76 kcal/mol. The imidazole N3 of 8k interacted with the Cyc919 residue of VEGFR-2, forming a hydrogen bond with a docking score of -9.03 kcal/mol. Moreover, compound 8k exhibited the best inhibitory activity on cell migration and wound healing. Conclusion: DES significantly improved the time and yield of the final reactions. Compound 8k, which showed the best cytotoxicity and inhibitory activity on cell migration, could be a suitable candidate for further structural optimization.